Improving the field accuracy of a malaria diagnostic algorithm combining sequential interpretation of rapid diagnostic test detecting PfHRP2 and pLDH in febrile children in a seasonal hyperendemic malaria transmission area in Burkina Faso - Diane Yirgnur Some; Francois Kiemde; Berenger Kabore; Daniel Valia; Toussaint Rouamba; Seydou Sawadogo; Athanase M. Some; Hermann Sorgho; Macaire Nana; Yacouba Nombre; Nadine A. Kone; Adelaide Compaore; et al. (PLoS ONE, 2026)
Objective To e valuate the field accuracy of a malaria diagnostic algorithm combining sequential interpretation of two-step malaria RDT detecting Pf HRP2 and p LDH with information on previous antimalarial treatments within the past four weeks for the diagnosis of malaria in febrile children under 5 years compared to standard diagnosis using a Pf HRP2 only based RDT. Methods Febrile children aged 6–59 months attending outpatient clinics were randomized to either the control group, which received the standard RDT ( Pf HRP2 only), or the intervention groups (an e-algorithm or a decisional algorithm), which was subjected to the diagnostic algorithm combining an RDT detecting Pf HRP2 and p LDH with information on previous antimalarial treatment. Malaria diagnosis with Pf HRP2-based RDT was reported as positive or negative. The sequential interpretation was reported as (i) positive when the p LDH line appeared, regardless of the Pf HRP2 results, (ii) negative when both lines did not appear and (iii) undetermined when only the Pf HRP2 line appeared, and information on previous antimalarial treatment within the past 4 weeks was used as a decision-support tool to classify active malaria from past infection. Blood samples were also collected for expert microscopy as the gold standard, and for qPCR to further evaluate undeterminate results and potential false-positive RDT outcomes. Results In total 1176 children were included, with 66.7% (784/1176) assigned to the intervention arms and 33.3% (392/1176) to the control arm. In patients assigned to the sequential algorithm, the number of undetermined cases was 12.7% (100/784). Considering microscopy as the gold standard, Pf HRP2-based RDT reported a sensitivity of 96.5% and a of specificity 79.1%, with positive and negative predictive values of 78.3% and 96.7%, respectively. For the sequential algorithm, the sensitivity, specificity, positive and negative predictive values of the conclusive-only results (i.e., Pf HRP2±/ p LDH+ and Pf HRP2-/ p LDH-) were 97.4%, 98.4%, 98.0% and 97.9%. However, when undetermined result were combined with conclusive results, the sensitivity, specificity, positive and negative predictive values were 89.7%, 96.8%, 95.6% and 92.4% respectively. Among recently antimalarial treated participants in sequential algorithm arm, 59.5% (50/84) were qPCR-positive, compared to 68.7% (11/16) qPCR-positivity in those without recent treatment. Conclusions The sequential diagnostic approach improves the diagnosis of malaria in a real world setting, compared to the use of Pf HRP2-(only) based RDT. However, relying only on history of antimalarial treatment in undetermined cases may decrease algorithm’s sensitivity, which could result in missing active or recurrent malaria infections.